Crisis Management: A Way Towards Being Human - Jha Avdhesh (Pamukkale Üniversitesi İşletme Araştırmaları Dergisi, 2020)
As an exploratory research, the study was conducted with an objective to create a simple and understandable process of crisis management. Based on the review of literature, it was hypothesized that people preparing for a crisis, face the barrier of helplessness but step ahead to pacify their needs. In order to obtain data, interviews were conducted with the masons, factory workers, house keepers, maids and servants, salaried people and businessmen who responded as the respondents. Content analysis, analysis and synthesis, grouping, mind mapping and thematic analysis was applied to understand the process of crisis management amongst the people. The analysis and synthesis method were used to group the similar responses. Based on this analysis, several reasons were identified and based on synthesis several deductions were made for mind mapping which led to the visual representation of the stages in the process of crisis management. Association analysis was applied to connect and develop the relationship amongst the stages as well study the influence of the actions in each stage. Using a mind map and content analysis, a logical sequence of the characteristics and their relationships within the entire crisis management process was established in five stages and nine sub-stages. Further research needs to be conducted to verify and ascertain the validity of the stages and sub-stages.